The Lived Experiences of Muslim Internally Displaced Persons in Cotabato City, Southern Philippines - Norodin Salam; Marwisa Sedik Salam; Aminullah Elhady (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2023)
The increasing number of cases of poverty and human-made disasters has exacerbated the issue of displacement in the previous years. Narratives of the experiences of the Internally Displaced Persons living in the cities have not been thoroughly reported at the local context. The purpose of this study is to describe the lived experience of the internally displaces persons currently residing in Cotabato City, Philippines. This research utilized mixed methods design in the triangulation of the results, quantitative approach was used in the first part of the study. Descriptive-qualitative data were gathered through Focused Group Discussion and in-depth interviews. Generally, this study discovered that IDPs consistently faced financial difficulties living with poverty in the rural areas, which motivated them to resettle and live in the urban areas. It was revealed that living in the city was definitely privileged for their peace of mind in terms of source of income which helped their husband sustained and augment their financial status, and inspired in religious gathering. Moreover, the IDPs preferred to stay in the city where their children pursue education, financially sustained, strengthen gender roles in Islamic teachings and access to health care services.